Why gender matters in COVID-19 responses: Now and in the future - Quisumbing, Agnes R.; Kumar, Neha; Meinzen-Dick, Ruth S.; Ringler, Claudia (International Food Policy Research Institute, 2020)
To contain the spread of COVID-19, health ministries and the World Health Organization (WHO) are advising everyone to keep up to date on latest developments, wash hands frequently, stay at home, and practice physical distancing when outside the home.1 These recommendations are inconveniences for most people in Europe or the United States, but for many in developing countries, even these basic precautions will be difficult to implement. Here are some ways these public health recommendations affect women and men differently in developing countries, particularly in rural areas — and some ideas for how to address the disparities.